RESILIENCE IN AGRICULTURE: IS THERE THEORETICAL AND METHODOLOGICAL CHAOS? - Marlena Grzelczak; Agnieszka Kurdyś-Kujawska; Michał Soliwoda (Polityki Europejskie, Finanse i Marketing)
The increasingly volatile conditions of doing business and the existence of societies are a clear reason to explore the category of resilience. The article aims to present and structure selected theoretical and methodological problems concerning resilience in agriculture. The results of a bibliometric analysis indicate a research gap referring to the category of financial resilience. The category of ‘resilience’ is based on relatively modern concepts from business management, particularly those close to risk management theory. Identifying and measuring capacities to build and strengthen resilience seems to be very important. Quantitative and qualitative methods may be used to explore the category ‘financial resilience’ in agriculture. There has been a noticeable research gap in agricultural finance to fill in. The indicator system for measuring the resilience of agricultural enterprises/farms has some limitations related to the aggregated nature of some financial categories. It would be advisable to develop a global measure of risk resistance in parallel (e.g., in the form of a synthetic index).